2016
DOI: 10.1091/mbc.e14-11-1555
|View full text |Cite
|
Sign up to set email alerts
|

Integration of linear and dendritic actin nucleation in Nck-induced actin comets

Abstract: The role of the Nck adaptor protein in balancing linear versus branched actin nucleation in comet tails is evaluated. Nck recruits both linear and branched nucleation-promoting factors, both of which are necessary for the formation of actin comets. The findings highlight a novel role for Nck in pathogen-like actin motility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…, 2010 ). Because Nck integrates dendritic and linear actin nucleation ( Borinskaya et al. , 2016 ), we propose that Nck coordinates the molecular machineries directing the assembly of the complex actin network enabling the protrusive function of invadopodia.…”
Section: Discussionmentioning
confidence: 99%
“…, 2010 ). Because Nck integrates dendritic and linear actin nucleation ( Borinskaya et al. , 2016 ), we propose that Nck coordinates the molecular machineries directing the assembly of the complex actin network enabling the protrusive function of invadopodia.…”
Section: Discussionmentioning
confidence: 99%
“…Formins, on the other hand, are thought to predominantly assemble actin bundles. However, accumulating data reveal a role of various formins in lamellipodial protrusion [1216] and other branched networks [17,18], where formins can function as elongators and/or nucleators of actin filaments. Specifically, mDia2 can stimulate both elongation and nucleation of actin filaments in protrusions [16], FMNL2 seems to mostly promote elongation of Arp2/3-nucleated filaments, whereas FMNL3 and mDia1 appear to be largely implicated in nucleation [14,15].…”
Section: Actin Cytoskeleton In Protrusionmentioning
confidence: 99%
“…Notably, although actin comet-like structures in MNCs do not resemble typical actin organization in non-neuronal cell types (Svitkina, 2018), such as stress fibers found in fibroblasts, epithelial and endothelial cells (Tojkander et al, 2012) or Arp2/3-dependent actin meshwork found in a variety of motile cells (Lehtimäki et al, 2016), they resemble filamentous actin structures propelling organelles such as endosomes and endocytic vesicles (Collins et al, 2011;Svitkina, 2018) and bacteria comet tails (Tilney and Portnoy, 1989;Cameron et al, 2000;Cameron et al, 2001;Svitkina, 2013). These structures are thought to be involved in organelle/vesicle trafficking and feature fast polymerizing actin filaments nucleated by Arp2/3 (Collins et al, 2011) or formins (Borinskaya et al, 2016). Future studies are needed to study dynamic properties of comet-like structures found in MNC somata and characterize their interacting partners, to determine if these comet-like filaments resemble axonal actin trails, organelle-propelling actin filaments, or represent a functionally distinct structure in MNCs that might be crucial for their unique physiology.…”
mentioning
confidence: 97%